Vitamin D supplementation in pregnancy, prenatal 25(OH)D levels, race, and subsequent asthma or recurrent wheeze in offspring: Secondary analyses from the Vitamin D Antenatal Asthma Reduction Trial - Wolsk, Helene M.; Harshfield, Benjamin J.; Laranjo, Nancy; Carey, Vincent J.; O'Connor, George; Sandel, Megan; Strunk, Robert C.; Bacharier, Leonard B.; Zeiger, Robert S.; Schatz, Michael; Hollis, Bruce W.; Weiss, Scott T.; et al. (Journal of allergy and clinical immunology, 2017)
Nutrient trials differ from drug trials because participants have varying circulating levels at entry into the trial. We sought to study the effect of a vitamin D intervention in pregnancy between subjects of different races and the association between 25-hydroxyvitamin D3 (25[OH]D) levels in pregnancy and the risk of asthma/recurrent wheeze in offspring. The Vitamin D Antenatal Asthma Reduction Trial is a randomized trial of pregnant women at risk of having children with asthma randomized to 4400 international units/d vitamin D or placebo plus 400 international units/d vitamin D. Asthma and recurrent wheezing until age 3 years were recorded. African American (AA) women (n = 312) had lower initial levels of 25(OH)D (mean [SD], 17.6 ng/mL [8.3 ng/mL]) compared with non-AA women (n = 400; 27.1 ng/mL [9.7 ng/mL], P < .001). No racial difference was found from vitamin D supplementation in pregnancy on asthma/recurrent wheezing in offspring (P for interaction = .77). Having an initial level of greater than 30 ng/mL and being randomized to the intervention group was associated with the lowest risk for asthma/recurrent wheeze by age 3 years compared with having an initial level of less than 20 ng/mL and receiving placebo (adjusted odds ratio, 0.42; 95% CI, 0.19-0.91). We did not find differences between AA and non-AA mothers in the effect of maternal vitamin D supplementation and asthma/recurrent wheeze in offspring at 3 years. Maternal supplementation of vitamin D, particularly in mothers with initial 25(OH)D levels of greater than 30 ng/mL, reduced asthma/recurrent wheeze in the offspring through age 3 years, suggesting that higher vitamin D status beginning in early pregnancy is necessary for asthma/recurrent wheeze prevention in early life. [Display omitted]